Development of ZnO Nanoflake Type Structures Using Silk Fibres as Template for Water Pollutants Remediation - Rao, K Jagajjanani; Korumilli, Tarangini; Kp, Akshaykumar; Wacławek, Stanisław; Černík, Miroslav; Padil, Vinod V T (Polymers, 2020)
We have fabricated ZnO nanoflake structures using degummed silk fibers as templates, via soaking and calcining the silk fibers bearing ZnO nanoparticles at 150 °C for 6 h. The obtained ZnO nanostructures were characterized using scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and UV-vis and fluorescence spectroscopic analysis. The size (~500-700 nm) in length and thicknesses (~60 nm) of ZnO nanoflakes were produced. The catalysis performances of ZnO nanoflakes on silk fibers (ZnSk) via photo-degradation of naphthalene (93% in 256 min), as well as Rose Bengal dye removal (~1.7 mM g-1) through adsorption from aqueous solution, were practically observed. Further, ZnSk displayed superb antibacterial activity against the tested model gram-negative Escherichia coli bacterium. The produced ZnSk has huge scope to be used for real-world water contaminants remediation applications.
Keywords: antibacterial efficiency; photo-degradation; silk fibers; ZnO; dye removal; nanoflakes